Implementation of IOT-Based Chili Plant Watering System Prototype with BLYNK Control - Cessi Rumondor; Mans Lumiu Mananohas; Rillya Arundaa; Eric Alfonsius (Universitas Teknokrat Indonesia, 2025)
This research aims to design and implement a prototype of an Internet of Things (IoT)-based dual-mode irrigation system for chili plants, integrating automatic and manual control via the Blynk application. The background of this study is the need for efficient water management in chili farming, which is often constrained by traditional manual irrigation methods. The system is built using a NodeMCU ESP32 microcontroller connected to a capacitive soil moisture sensor, DHT11 sensor, and relay modules that control water and fertilizer pumps. The research method uses a prototyping model to design, build, and test the irrigation system. Real-time sensor data is transmitted to the Blynk dashboard, allowing farmers to monitor environmental conditions and control the pumps either automatically (based on threshold logic) or manually via smartphone. The calibration results show that the soil moisture sensor achieves 93.5% accuracy. Testing using the black-box method confirms that all system components function as expected, with responsive performance both in automatic and manual modes. The findings demonstrate that the dual-mode IoT-based irrigation system can maintain optimal soil moisture levels while providing flexibility for farmers to override the system based on real-world conditions. This hybrid solution offers a practical approach to modern agriculture, improving decision-making and efficiency in crop watering practices.